Health-related quality of life in congenital heart disease surgery patients in Pakistan: protocol for a mixed-methods study. Issue 10 (30th October 2017) - Ladak, Laila Akbar; Hasan, Babar Sultan; Gullick, Janice; Awais, Khadija; Abdullah, Ahmed; Gallagher, Robyn
Abstract : Introduction: Reduced health-related quality of life (HRQOL) has been reported in postoperative patients with congenital heart disease (CHD). However, there is a paucity of data from low-income and middle-income countries (LMIC). Differences in sociodemographics and sociocultural contexts may influence HRQOL. This protocol paper describes a study exploring HRQOL in surgical patients with CHD from a tertiary hospital in Pakistan. The study findings will assist development of strategies to improve HRQOL in a resource-constrained context. Methods and analysis: This prospective, concurrent triangulation, mixed-methods study aims to compare HRQOL of postsurgery patients with CHD with age-matched healthy siblings and to identify HRQOL predictors. A qualitative component aims to further understand HRQOL data by exploring the experiences related to CHD surgery for patients and parents. Participants include patients with CHD (a minimum of n 95) with at least 1-year postsurgery follow-up and no chromosomal abnormality, their parents and age-matched, healthy siblings. PedsQL 4.0 Generic Core Scales, PedsQL Cognitive Functioning Scale and PedsQL 3.0 Cardiac Module will measure HRQOL. Clinical/surgical data will be retrieved from patients' medical files. Student's t-test will be used to compare the difference in the means of HRQOL between CHD and siblings. Multiple regression will identify HRQOL predictors. A subsample of enrolled patients (n 20) and parents (n 20) from the quantitative arm will be engaged in semistructured qualitative interviews, which will be analysed using directed content analysis. Anticipated challenges include patient recruitment due to irregular follow-up compliance. Translation of data collection tools to the Urdu language and back-translation of interviews increases the study complexity. Ethics and dissemination: Ethics approval has been obtained from The Aga Khan University, Pakistan (3737-Ped-ERC-15). Study findings will be published in peer-reviewed journals and presented at national and international conferences.